Catalisadores de Pd suportados em La2O3-Al2O3 para a reforma do metano: influência do La na estrutura superficial, atividade e estabilidade - Cassinelli, Wellington Henrique (2006)
The steam reforming methane reaction catalysed by Pd/(x)La2O3-Al2O3 was studied using different contents of La. The Pd(x)La2O3-Al2O3 catalysts were obtained by wetness impregnation of alumina with an aqueous solution of Pd(NO3)2 and were characterized by specific surface area and pore volume measurements (SBET e Vp), x-ray diffraction (XRD), temperature programmed reduction (TPR), metallic dispersion measurements, diffuse reflectance spectroscopy at the UV-visible region (DRS) and diffuse reflectance infrared Fourier-transform spectroscopy (DRIFTS) of adsorbed CO. The SBET and Vp results suggest that lanthanum is dispersed at the γ-Al2O3 surface without blocking the support pores with La addition up to 12 wt%. The TPR and DRIFTS-CO results for Pd/Al2O3, show that there is an increase in the PdO-support interaction and the formation of Pd0 surfaces where the CO adsorbs preferentially at the linear form if compared to bridged CO species. Pd dispersion results and DRIFTS-CO for the Pd/(x)La-Al2O3 catalysts suggest that with increasing La loading, there is a partial recover of Pd sites by lanthanum oxide species resulting in changes at the CO adsorption form and lower accessibility to Pd sites due to geometric effects caused by the presence of LaOx compounds at the surface of Pd0 particles. Pd dispersion data and the catalytic activity tests show that with increasing La content up to 12 wt%, there is a decrease in Pd dispersion, followed by an increase in the specific activity, an increase in TOF values and lower apparent activation energies for CH4 during steam reforming. The higher activity of this catalysts with increasing La loading can be related to the following factors: i) the formation of a fraction of sites with higher electronic density; and ii) the transference of species like O* from the support to the Pd surface, that would promote the removal of species like C* adsorbed at Pd sites with high electronic density. This will therefore result in higher activities and higher accessibility of CH4 to Pd sites.